Heritage of 2014 Winter Olympics in sochi: sociological analysis - Galeev, A. R.; Dulina, N. V.; Ikingrin, Ye. N.; Davydova, S. A.; Korichko, Yu. V.; Lubysheva, L. I. (Theory and Practice of Physical Culture, 2019)
It was for the first time in 1980 that our country hosted Olympic Games in Moscow, and the second chance came in 2014 with the Winter Olympic Games in Sochi. The article analyzes the questionnaire survey data on issues of the 2014 Winter Olympic Games. The survey showed multiple benefits of the 2014 Winter Olympics for the interregional and international cooperation projects and global image of the host city, region and country on the whole. Olympic Games hosting is always a great honor and responsibility for the country elected by the global communities. The first Olympics were hosted by the nation in the Soviet times and the second by the modern Russia. The new times and huge reforms for the period gave some reasons for doubts on whether or not the nation can cope with the top-ranking sport event hosting challenges. Nowadays, five years after the 2014 Winter Olympic Games, we have every reason to believe that Russia demonstrated great success and surprised the world by its new image, great opportunities, event design and management skills and technologies, and the genuine hospitality and friendliness. The questionnaire survey data showed that the top-ranking sport events like the 2014 Winter Olympic Games may give a great boost to the local and global health cultures of new generations, sport infrastructure development projects, and for the progress and global image of the host city and nation on the whole.